2020
DOI: 10.1089/scd.2020.0024
|View full text |Cite
|
Sign up to set email alerts
|

Treating Ischemically Damaged Porcine Kidneys with Human Bone Marrow- and Adipose Tissue-Derived Mesenchymal Stromal Cells During Ex Vivo Normothermic Machine Perfusion

Abstract: Pre-transplant normothermic machine perfusion (NMP) of donor kidneys offers the unique opportunity to perform active interventions to an isolated renal graft prior to transplantation. There is increasing evidence that mesenchymal stromal cells (MSCs) could have a para-/endocrine regenerative effect on ischaemia-reperfusion injury. The purpose of this study was to determine which cytokines are secreted by MSCs during NMP of a porcine kidney. Viable porcine kidneys and autologous whole blood were obtained from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
0
30
0
1
Order By: Relevance
“…In their subsequent study, they found a significantly increased level of hepatocyte growth factor, together with a decrease in neutrophil gelatinase-associated lipocalin (NGAL) and lactic dehydrogenase in the perfusate. This evidence indicates that Cao et al (2020) the infusion of MSCs during NMP can protect the isolated kidney from ischemic damage (Pool et al 2020).…”
Section: Mscs In Renal Recoverymentioning
confidence: 89%
“…In their subsequent study, they found a significantly increased level of hepatocyte growth factor, together with a decrease in neutrophil gelatinase-associated lipocalin (NGAL) and lactic dehydrogenase in the perfusate. This evidence indicates that Cao et al (2020) the infusion of MSCs during NMP can protect the isolated kidney from ischemic damage (Pool et al 2020).…”
Section: Mscs In Renal Recoverymentioning
confidence: 89%
“…Experimental evidence for the delivery of MSCs [13–15], gene therapies [28], nanoparticles [30,31] and other IRI targeted [33–39] therapies during NMP is increasing and the results have been positive. However, none of the approaches have been tested in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the most recent study by the group, they found that the MSCs increased reparative processes in porcine kidneys during NMP. There was an increase in immunomodulatory cytokines (IL‐6 and IL‐8) and hepatocyte growth factor, and a reduction in injury markers, lactate dehydrogenase and neutrophil gelatinase‐associated lipocalin (NGAL) during perfusion [15].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Porcine kidneys challenged with warm ischemia and subsequent HMP were perfused under normothermic conditions for 7 h. After 1 h of NMP, either 10 7 human aMSCs or 10 7 bmMSCs were added. The authors demonstrated that the addition of both types of human MSCs to an ischemically damaged porcine kidney led to an increased release of immunomodulatory cytokines such as human hepatocyte growth factor (HGF), IL-6, and IL-8 into the perfusate, as well as reduced levels of organ injury markers such as lactate dehydrogenase (LDH) and neutrophil gelatinase-associated lipocalin (NGAL), compared to controls without MSC treatment [ 90 ].…”
Section: Mscs In Organ Machine Perfusionmentioning
confidence: 99%